2001
DOI: 10.1093/hmg/10.17.1859
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an endogenous RNA transcribed from the antisense strand of the HFE gene

Abstract: Hereditary haemochromatosis is an autosomal recessive disease which results in iron overload, and it is the most frequently inherited disorder in Caucasian populations. The gene involved (HFE) has recently been identified, and it encodes an MHC class I-like molecule. A 2.7 kb cDNA has been isolated, whereas the HFE gene expression is characterized by an almost ubiquitous mRNA of 4.1 kb in size. The difference between this transcript and the isolated cDNA has not yet been explained. Thus, the 5' end of the HFE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Such a regulation has been described in vivo for the FGF-2 47 and HFE genes. 48 We could identify some putative promoter elements correlating with the conserved regions in silico. But, since the reliability of the available prediction algorithms is not very high, this possibility remains to be tested experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…Such a regulation has been described in vivo for the FGF-2 47 and HFE genes. 48 We could identify some putative promoter elements correlating with the conserved regions in silico. But, since the reliability of the available prediction algorithms is not very high, this possibility remains to be tested experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…An example of this method of antisense regulation is the inhibition of alternative splicing induced by the RevErbA␣ transcript in different B-cell lines, which overlaps one of two functionally anatagonistic splice forms of the thyroid hormone receptor ErbA␣2 mRNA (Hastings et al 1997(Hastings et al , 2000. An antisense RNA-based mechanism has also been shown to be responsible for the regulation of the human HFE gene, which is implicated in iron metabolism and involved in the human inherited disorder hereditary hemochromatosis (Thenie et al 2001). Although there is no direct evidence for the role of the HFE antisense transcript in vivo, in vitro studies demonstrated that the antisense transcript represses the translation of the HFE mRNA (Thenie et al 2001).…”
Section: Rna Maskingmentioning
confidence: 99%
“…An antisense RNA-based mechanism has also been shown to be responsible for the regulation of the human HFE gene, which is implicated in iron metabolism and involved in the human inherited disorder hereditary hemochromatosis (Thenie et al 2001). Although there is no direct evidence for the role of the HFE antisense transcript in vivo, in vitro studies demonstrated that the antisense transcript represses the translation of the HFE mRNA (Thenie et al 2001). …”
Section: Rna Maskingmentioning
confidence: 99%
“…The following are known mammal cDNA sequences reported to accompany antisense transcripts selected from the recent literature and used in this study: Fgf2 (Knee et al 1997), Hif1a (Thrash-Bingham and Tartof 1999), Tgfb2 (Coker et al 1998), Tnfrsf17 (Hatzoglou et al 2002), Mkrn2 (Gray et al 2001), Hfe (Thenie et al 2001), Klhl1 (Benzow and Koob 2002), Ucn (Shi et al 2000), Wt1 (Moorwood et al 1998), Tnni1 (Podlowski et al 2002), Thra (Hastings et al 2000), Hsp70.2 (Murashov and Wolgemuth 1996), Hoxd-3 (Bedford et al 1995), Tyms (Dolnick 1993), CD3z (Lerner et al 1993), N-myc (Krystal et al 1990), Trp53 (Khochbin and Lawrence 1989), Ercc1 (van Duin et al 1989), and Hoxa11 (Hsieh- Li et al 1995). To identify the known sense-antisense transcripts in the bidirectional transcription pairs calculated in this article, we looked up the GenBank# or Refseq# of the known transcripts in the redundant version of our pair list.…”
Section: A List Of Known Sense Transcripts With Antisense Transcriptsmentioning
confidence: 99%